Peranan Kompetensi dalam Meningkatkan Kinerja Guru pada Proses Belajar Siswa di SMK N 1 Singaraja - Damayanti, Ni Luh Rani; Irwansyah, M. Rudi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
Teacher competence is of course very important in a student learning process. This study aims to describe the role of competence in improving teacher performance in the student learning process at SMK N 1 Singaraja using a descriptive design. The subjects in this research were 30 teachers at SMK Negeri 1 Singaraja. The object of this research is to describe the role of competency in improving teacher performance in the student learning process at SMK N 1 Singaraja. The data collection instruments used in this research were observation, semi-structured interviews, and documentation. The research results show that pedagogic, personality, professional, social competence plays an important role in improving teacher performance in the student learning process).